The Development of Agro-Tourism Based on Arabica Coffee Plantation in Bali - YUDHARI, I Dewa Ayu Sri; DARWANTO, Dwidjono Hadi; WALUYATI, Lestari Rahayu; MULYO, Jangkung Handoyo (Journal of Environmental Management and Tourism; Vol 11 No 1 (2020): JEMT Volume XI Issue 1(41) Spring 2020, 2020)
The agricultural sector plays an important role in the economic style of Kabupaten Bangli, where the population depends on their livelihood as farmers mostly. The tourist attraction of the tourism sector in agriculture is the magnetism of Arabica Coffee agro-tourism. The area of Arabica coffee plantations in Kabupaten Bangli in Bali which covers more than 1883.92 hectares as a whole. One of the districts (kecamatan) in Kabupaten Bangli that has the largest area of Arabica coffee plantations is Kecamatan Kintamani, which is around 1,836 hectares with 2017 production amounting to 2,112 tons per hectare per year. This is the area of coffee plantations which is the largest and with the highest amount of production among other districts in Kabupaten Bangli. This has the potential to support agro-tourism based on Arabica coffee plantations. The method used in this study is qualitative using mathematical operations. In this study, data analysis using AHP (Analytical Hierarchy Process) data analysis techniques with the help of expert choice 11 software. The purpose of this study is to examine agro-tourism development strategies which are based on actors, factors, objectives, and alternative strategies for developing Arabica Coffee agro-tourism in Kabupaten Bangli, Bali.